Imag(in)ing 'good' Swedish meat: gender, sexuality, race and nation in the sale of higher welfare chicken. Issue 11 (2nd November 2018) - Petitt, Andrea; Bull, Jacob
Abstract: This article attends to the ways that meat from higher welfare chicken is sold in supermarkets in Sweden. Recognising that the 'welfare-friendly chicken body is an achievement between the market, the animal and publics', this article continues these discussions to show how gender, sexuality, race and nation operate within these markets and publics by looking at how welfare is marketed in chicken meat sales, particularly higher welfare chicken, compared to other meat. By attending to the images used to sell chicken, we examine how ideas about 'the farm' and 'the family' are mobilised in the supermarket. Using images of specific families, they position chicken both in the Swedish rural landscape and in intersecting social categories. These two narratives intertwine and operate as a device in the sale of high welfare chicken meat. This, we argue, hides the dependency on global supply chains and workforce, but also (re)produces ideas about what high welfare is, who cares, and how we should care. Throughout the article, we demonstrate how the narratives of farm, family, and nation operate in relation to species and welfare, as the 'Swedish family farm' is imag(in)ed to sell high welfare chicken in ways that contrast with meat from other animals.